The Influence of Training Education and Educator Competency on Educator Performance Through Organizational Support as Mediation Variables at the South Sulawesi ini Police School - Muliadi, Muliadi; Idris, Muhammad (Economics and Business Journal (ECBIS), 2022)
This study aims to analyze the effect of education and training on organizational support at the National Police School (SPN) Polda South Sulawesi, the effect of educator competence on organizational support, the effect of education and training on educator performance, the influence of educator competence on educator performance, the effect of organizational support on performance. educators, the effect of organizational support as a mediating variable on the effect of education and training, and organizational support as a mediating variable on the effect of educator competence on educator performance by taking 46 employees as research samples. The results of this study indicate that (1) Based on the results of statistical tests, it is known that education and training have a significant effect on organizational support, and the competence of educators has a significant effect on organizational support at the State Police School (SPN) Polda South Sulawesi; (2) Based on the results of statistical tests, it is known that education and training, educator competence and organizational support have a significant effect on the performance of educators at the State Police School (SPN) Polda South Sulawesi; (3) Based on the results of statistical tests, it is known that organizational support as a mediating variable has a significant effect on education and training while organizational support as a mediating variable has no effect on educator competence on educator performance at the State Police School (SPN) Polda South Sulawesi. This means that organizational support can directly affect education and training, while organizational support does not indirectly affect the competence of educators on the performance of educators at the National Police School (SPN) Polda South Sulawesi.